Seleção de materiais poliméricos para blindagem de baterias de carros elétricos - Prado, João Otávio Gomes de Oliveira (Universidade Federal de São Carlos, 2023)
Electric vehicles (EVs) are an increasingly imminent reality, given the behind-thescenes efforts by major automakers to comply with new environmental regulations and enhance mobility efficiency. When considering an EV, two components are the primary subjects of study for improvement: the electric motor and the batteries. The main challenges in the sector are to provide safety and reliability in a new technology. One of these challenges is to provide solutions for electromagnetic shielding of Li-ion batteries. To achieve this, an enclosure is used to protect these batteries, and commonly, they are manufactured using metallic alloys. These covers are susceptible to mechanical loads, high impact forces (collisions), thermal instability (fires), and electromagnetic interference. Due to market demand, efficiency with low weight is sought, highlighting specific properties. In this context, polymeric materials have emerged as potential candidates for such applications. The focus of this study was to discuss the possibility of replacing conventional metallic alloys with polymer matrix materials, leveraging the low material density. Thus, the conventional Ashby methodology was applied to maximize electrical conductivity and toughness while reducing density and cost. As a result, a class of candidates was identified, mainly based on thermoplastic matrices reinforced with carbon fibers. These materials proved suitable for use in this application. However, a critical analysis of their commercial feasibility is necessary. In addition to discussing this issue, the current landscape of the polymer material development industry for electromagnetic shielding of electric car batteries was also analyzed.
Selection of polymeric materials for emi shielding electric cars batteries
Keywords: Baterias; Blindagem; Veículos elétricos; Polímeros; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS